2023
DOI: 10.1186/s12893-023-02178-1
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive surgical approach with vascular resection and reconstruction for retroperitoneal sarcomas: a systematic review

Hankui Hu,
Qiang Guo,
Jichun Zhao
et al.

Abstract: Background and aim Surgery is the mainstay of treatment and completeness of surgical resection is critical to achieve local control for retroperitoneal sarcoma (RPS). En-bloc resection of adjacent organs, including major abdominal vessels, is often required to achieve negative margins. The aim of this review was to summarise the available evidence to assess the relative benefits and disadvantages of an aggressive surgical approach with vascular resection in patients with retroperitoneal sarcoma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Our study showed similar 5-year LRFS and OS rates between patients with and without the vascular resection in the matched cohort (LRFS: P = 0.74, OS: p = 0.12, respectively). This finding was comparable to those reported by Hu et al (Hu et al 2023 ) and Blair et al (Blair et al 2018 ). Vascular resection was also not an independent predictor influencing LRFS and OS in patients with RLPS.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed similar 5-year LRFS and OS rates between patients with and without the vascular resection in the matched cohort (LRFS: P = 0.74, OS: p = 0.12, respectively). This finding was comparable to those reported by Hu et al (Hu et al 2023 ) and Blair et al (Blair et al 2018 ). Vascular resection was also not an independent predictor influencing LRFS and OS in patients with RLPS.…”
Section: Discussionsupporting
confidence: 92%
“…The meta-analysis showed that vascular resection did not improve RFS or OS compared with tumor resection alone. Vascular resection was also associated with a higher rate of major complications in one study, but no deaths were reported in two studies (19). When managing an intracardiac tumor thrombus, resection is preferred and intraoperative CPB should be considered to facilitate resection and maintain perfusion (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%